2022
DOI: 10.1097/ncq.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

Improved 30-Day Heart Failure Readmissions Following Implementation of an Advanced Cardiovascular Education (ACE) Academy

Abstract: Background: Heart failure readmissions are common, though some are preventable through evidence-based management. Local Problem: Despite outperforming national benchmarks for 30-day readmissions, compliance with an evidence-based institutional heart failure management pathway was inconsistent. The purpose of this project was to reduce 30-day heart failure readmission rates through an educational intervention and an electronic health record (EHR) redesign. Methods: The cardiac services nursing leadership te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Of these studies, detailed assessments resulted in the review of 15 studies meeting all inclusion criteria. Out of the 15 studies, 10 studies utilized quantitative design (Carthon et al, 2015;Gilbert et al, 2021;Hoyer et al, 2018;Kara et al, 2015a;Lasater & Mchugh, 2016;Ma et al, 2015;Mathews et al, 2014;McHugh & Ma, 2013;Oliver et al, 2022;Shirey et al, 2019), and five utilized a qualitative approach (Coyne et al, 2016;Feo et al, 2022;Glette et al, 2018;Okoniewska et al, 2015;Udod et al, 2022). For search strategy, see Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these studies, detailed assessments resulted in the review of 15 studies meeting all inclusion criteria. Out of the 15 studies, 10 studies utilized quantitative design (Carthon et al, 2015;Gilbert et al, 2021;Hoyer et al, 2018;Kara et al, 2015a;Lasater & Mchugh, 2016;Ma et al, 2015;Mathews et al, 2014;McHugh & Ma, 2013;Oliver et al, 2022;Shirey et al, 2019), and five utilized a qualitative approach (Coyne et al, 2016;Feo et al, 2022;Glette et al, 2018;Okoniewska et al, 2015;Udod et al, 2022). For search strategy, see Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…A review of the study designs across this group of quantitative articles revealed notable limitations and flaws that threatened the internal and external validity of research findings. Out of the 10 studies, 5 used quasi-experimental design (Hoyer et al, 2018;Kara et al, 2015a;Mathews et al, 2014;Oliver et al, 2022;Shirey et al, 2019) and 1 used randomized controlled trial (Gilbert et al, 2021), other 4 used a descriptive cross-sectional design. Since the majority of the studies used a cross-sectional design, establishing temporal precedence was not possible; thus, the ability to determine the causal relationship between leadership and readmission was limited.…”
Section: Characteristics Of the Quantitative Studiesmentioning
confidence: 99%
See 3 more Smart Citations